Are there differences between de novo and secondary upper tract urothelial carcinoma tumors? - Goldberg, Hanan; Cheung, Douglas C.; Chandrasekar, Thenappan; Klaassen, Zachary; Wallis, Christopher J.D.; Kulkarni, Girish S.; Sayyid, Rashid; Evans, Andrew; Masoomian, Mehdi; Bapat, Bharati; et al. (Canadian Urological Association Journal, 2018)
Introduction: Upper tract urothelial carcinoma (UTUC) accounts for <5% of all urothelial cancers. We aimed to ascertain the clinical differences between UTUC tumous presenting de novo (DnUTUC) and those presenting secondary (SUTUC) following a bladder cancer diagnosis. Methods: Our institutional database was queried for all UTUC patients who were surgically treated with radical nephroureterectomy or ureterectomy between 2003 and 2017. Bladder recurrence and cancer-specific mortality were compared. To reduce the possible bias due to confounding variables obtained from a simple comparison of outcomes, DnUTUC patients were matched (for age, gender, tumor location, type of surgery, grade, TNM staging, presence of carcinoma in situ, and lymphovascular invasion) with propensity score to SUTUC patients. Bladder recurrence and cancer-specific mortality were assessed with Cox proportional hazards model. Results: A total of 117 UTUC patients were identified: 80 with DnUTUC (68.4%) and 37 with SUTUC (31.6%). A greater proportion of males with SUTUC was demonstrated (89.2% vs. 68.8; p=0.02). In both groups, 67.5% of patients had high-grade disease but SUTUC demonstrated a higher carcinoma in situ rate (43.2% vs. 25%; p=0.047). Univariate analysis demonstrated that the fiveyear bladder recurrence rate was trending to be higher in SUTUC (65.3% vs. 20.5%; p=0.099). In the Cox model, however, it was associated with increased bladder recurrence (hazard ratio [HR] 3.69; 95% confidence interval [CI] 1.68–8.09; p=0.001). Although univariate analysis demonstrated that SUTUC patients were more likely to die of their disease (30.6% vs. 9%; p=0.009), the multivariable Cox model did not demonstrate this association. The limitations of this study include its retrospective, single-center design and relatively small cohort of patients. Conclusions: In this hypothesis-generating study, some evidence suggests that further research is needed to delineate differences between SUTUC and DnUTUC.